Elevated Serum Neopterin is Associated with Increased Risk of Cardiovascular Events in Acute Coronary Syndromes - Anwar Santoso; Sri Wardani; Ketut Surayana (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Neopterin is a soluble biomarker of monocyte activation and its increased concentration might be expressed in atherosclerosis. Until recently, there has been lacking of information on the prognostic role of neopterin in acute coronary syndromes (ACS). The study was aimed at measuring the associations between elevated serum neopterin and increased risk of cardiovascular (CV) events in ACS.METHODS: This was a prospective cohort study, recruited 71 ACS patients from January 31 through August 31, 2007 in Sanglah Hospital of Udayana School of Medicine, Denpasar – Bali. Cardiovascular events, such as: CV death, recurrent myocardial infarction, stroke and recurrent myocardial ischemia were previously defined. Relative risk and survival rate were measured successively by Cox proportional model and Kaplan-Meier curve.RESULTS: Of 71 ACS patients aged 56.8 ± 9.5 years, 21 (29.5%) subjects underwent CV events. Overall mean followup was 151.6 (95% CI: 129.7 – 173.5) days. Baseline characteristic were similarly distributed between groups with the highest quartile neopterin level (≥ 14.7 nmol/L) than those with lowest quartile (≤ 6.2 nmol/L). Patients with the highest quartile had the worst survival curve than those with the lowest quartile (log-rank test; P = 0.047). On Cox proportional model, relative risk of highest quartile group was 5.84 (95% CI: 1.19 – 28.47; P = 0.029) compared to lowest quartile, after being adjusted with other predictors.CONCLUSIONS: Elevated serum neopterin is associated with increased risk of CV events in acute coronary syndromes.KEYWORDS: neopterin, cardiovascular events, acute coronary syndromes